Advancing Environmental Justice By Expanding The Literary Canon - Von Blum, Paul (American & British Studies Annual, 2025)
Review of Petr Kopecký and Jan Beneš, eds. Environmental Justice in Ethnic American Literature (Lanham: Lexington Books, 2025)